Pengaruh Disiplin Kerja dan Keselamatan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan di PT. Bineatama Kayone Lestari Tasikmalaya - Cahya Thoatilah Sobarudin (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
The purpose of this study was to determine the effect of work discipline and occupational safety and health simultaneously on the work productivity of employees at PT. Binetama Kayone Lestari Tasikmalaya in the Blockboard Division, to determine the effect of work discipline partially on employee work productivity at PT. Bineatama Kayone Lestari Tasikmalaya in the Blockboard Division, to determine the effect of occupational health safety partially on employee work productivity at PT. Binetama Kayone Lestari Tasikmalaya in the Blockboard Division. The samples in this study were employees of PT. Bineatama Kayone Lestari Tasikmalaya in the Blockboard Division, totaling 100 people. The data collection method in this study was carried out using a questionnaire data collection technique, then testing the data with multiple linear regression analysis. The results showed that work discipline and occupational safety and health simultaneously had a significant effect on the work productivity of employees at PT. Binetama Kayone Lestari Tasikmalaya in the Blockboard Division, partially work discipline has a significant effect on employee work productivity at PT. Bineatama Kayone Lestari Tasikmalaya in the Blockboard Division, partially occupational health safety has a significant effect on employee work productivity at PT. Binetama Kayone Lestari Tasikmalaya in the Blockboard Division.